PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN MINAT BELAJAR IPS PADA SISWA KELAS V SDN 001 BATANG PERANAP KABUPATEN INDRAGIRI HULU (Jurnal Ilmu-Ilmu Sejarah, Budaya Dan Sosial ( LENTERA ), 2015)
From observation and experience in Class V Batang Peranap SDN 001 IndragiriHulu encountered symptoms, especially in social studies is of 23 students only 11 (47.8%) ofstudents are serious in taking into account social studies underway, while other students do notpay attention to the lesson . Based on the researchers interested in conducting a class actionresearch to determine appropriate action in the implementation of STAD cooperative learningto improve student interest in social studies class V SDN 001 Batang Peranap.Classroom action research was conducted in Class V Batang Peranap SDN 001 Indragiri Huluacademic year 2013/2014 the number of students as many as 23 people. This research wasconducted in two cycles starting from April 2013 to May 2013.Based on the results of the discussion of the number of students who completed the prasiklusonly 28% and increased in the first cycle to 70% in the first cycle sebebakan for both studentsand researchers are still in a period of adaptation and still requires some dokongan from variousparties. Seen on the second cycle increased to 88% with an average value that is 77.6 can beconcluded that the hypothesis proposed action can be accepted as true. In other words, that theapplication of cooperative learning model Jigsaw mode can improve studentsâ learning outcomesIPS SDN 001 Class V Batang Peranap Indragiri HuluKeywords: Cooperative Learning Model STAD, results of social studies.PENDAHULUAN